World Food Day 2025: IITA’s commitment to a hunger-free Africa - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
This World Food Day, we celebrate the farmers, scientists, and communities working together to nourish a growing world. From the soil to the table, from research labs to rural fields, every hand plays a part in feeding the future.